Questões sociocientíficas sobre mineração no ensino de ciências: uma proposta para a educação básica - Pereira, Bárbara Lopes Schiavetti Guimarães (2020)
In view of the political, cultural and social transformations of recent years, children must be prepared to develop attitudes of conscious and responsible attitude in situations that demand ethical and socio-environmentally just positions. The school environment is the appropriate place for the development of the skills necessary for the formation of critical and active citizens, trained to transform the environment in which they live. The achievement of these skills, as well as scientific literacy, can be made possible by the use of Sociocientific Questions (QSC) in science teaching. In this sense, the objectives of this research were: 1) To identify and compare the understanding and use of QSC by undergraduate students of Physics, Chemistry and Biology at PIBID / UFRN in initial teacher education; 2) Assess the limits and potential of a teaching sequence with QSC to contribute to the process of scientific literacy; and 3) Produce instructional didactic material for science teachers related to the theme “Ethical, economic and socio-environmental aspects of mining”. To this end, a questionnaire was applied to 19 undergraduates in Biology, 23 in Physics and 25 in Chemistry; and a didactic sequence was developed and applied to 9th grade students at a state school in the city of Natal / RN. Bardin's content analysis was used to treat the data obtained. The results showed that more than 90% of graduates had not worked with QSC; only four in total declared to have had experience with QSC; the most cited controversial topics were abortion and sexuality; and 88% of QSC citations related to the ecological / environmental aspect were carried out by Biology graduates. As for the didactic sequence, it was observed that the students obtained improvement in the skills of logical reasoning, critical sense, orality, and ability to argue. In addition, the analysis of comparative data of initial and final hypotheses according to Bybee (1995) revealed that, in general, the initial hypotheses received only 'nominal-2' and 'functional' classifications, whereas, after the development of the activities, the final hypotheses also received the classifications' conceptual / procedural 'and' multidimensional ', which proved progress in the students' scientific literacy process. Finally, it is believed that the instructional manual elaborated can contribute as a tool to help the teacher because it corresponds to the expectations consistent with an investigative teaching with thematic approach of QSC, since this proved to be an adequate strategy for teaching Science for the citizenship.